Monazite smelting integrated comprehensive recovery technology based on FJH
By using flash Joule heating technology to perform high-temperature instantaneous reduction pyrolysis of monazite and reducing carbon powder balls, combined with oxidation and acid dissolution separation, the problems of low resource recovery rate and high safety hazards in monazite rare earth ore have been solved, realizing a highly efficient recovery of rare earth, uranium and thorium and an environmentally friendly smelting process.
Patent Information
- Application Number
- CN202511204945.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-12-12
AI Technical Summary
Existing technologies for the extraction of monazite rare earth minerals suffer from problems such as large wastewater volume, low resource recovery rate, failure to recover uranium and thorium, high cost of radioactive waste disposal, high energy consumption, and significant safety hazards. In particular, the defects of traditional alkaline dissolution processes and high-temperature pyrometallurgical pretreatment have not been effectively addressed.
Flash Joule heating (FJH) technology is used to press monazite and reducing carbon powder into balls for high-temperature instantaneous reduction and cracking, which destroys the crystal structure of insoluble xenotime phosphate. Oxygen-enriched air is introduced to oxidize phosphoric acid, and the tail gas is washed with water to recover phosphoric acid. Combined with acid dissolution and extraction separation, the efficient recovery of rare earth, uranium and thorium is achieved.
It improves the recovery rate of rare earth and radioactive elements, reduces energy consumption, reduces the burden of waste liquid and waste residue treatment, avoids the safety hazards of white phosphorus, and realizes efficient and comprehensive resource recovery and an environmentally friendly smelting process.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of environmental protection, and particularly relates to an integrated comprehensive recovery process for extracting rare earth products, uranium, thorium and phosphorus products from monazite rare earth ore. BACKGROUND
[0002] Monazite is a typical associated radioactive mineral rich in rare earth, uranium and thorium. On the one hand, monazite contains 15 kinds of rare earth elements, with both light and heavy rare earth characteristics, and the rare earth content is about 55%, which is one of the important rare earth minerals. On the other hand, monazite contains radioactive elements uranium (about 0.3% to 0.5%) and thorium (about 4% to 12%), and the uranium content is one order of magnitude higher than the current uranium ore grade of most uranium mines, which is a typical associated uranium resource. Due to the high activity concentration of natural radionuclides of uranium and thorium in monazite, the transportation, storage, smelting and waste disposal of monazite should pay high attention to the radiation protection of workers and the radiation risk of the surrounding environment.
[0003] At present, the production process of monazite rare earth ore for extracting rare earth is mainly alkali method. In the reaction process of monazite rare earth ore and liquid alkali, rare earth generates water-insoluble rare earth hydroxide, and phosphorus reacts into trisodium phosphate. The rare earth hydroxide is then dissolved by hydrochloric acid to obtain rare earth chloride. The main problems of this process are large amount of wastewater, complex process, low resource recovery rate, no recovery of uranium and thorium resources, and high cost of disposal of radioactive waste residues.
[0004] Integrated comprehensive recovery technology has been studied to recover uranium and thorium resources. For example, Hunan Zhonghe Jin Yuan New Material Co., Ltd. uses alkali conversion, acid dissolution, extraction or resin adsorption to extract uranium, adjusts the pH to precipitate thorium hydroxide, removes impurities, and concentrates to produce mixed rare earth chloride. Or alkali conversion, acid dissolution, acid dissolution to pH 4 to recover mixed rare earth chloride, and then continue acid dissolution to pH 2 to dissolve uranium and thorium, recover uranium, and precipitate thorium. The process has the following problems: large amount of wastewater, radioactive wastewater, difficult to treat, complex process, low resource recovery rate, rare earth comprehensive recovery rate of about 94%, uranium / thorium not recovered, and high cost of disposal of radioactive waste residues. The main reason is that the alkali conversion process has acid-insoluble slag, which leads to a large amount of Y (yttrium) resources that cannot be recovered, and the crystal always contains 0.3% of uranium resources that cannot be recovered.
[0005] Some studies have employed pyrometallurgical pretreatment of monazite, such as the patent application CN2022110249918, which proposes high-temperature treatment of monazite to recover phosphorus and rare earth products. The problems with this approach are: high pretreatment temperatures (above 1300 degrees Celsius), high energy consumption, and failure to achieve comprehensive utilization of uranium and thorium resources during the recovery process; furthermore, despite the high reaction temperatures, phosphate crystals of important rare earth elements such as Dy are not fully opened, leading to significant economic losses due to the inability to recover them through acid dissolution; additionally, the inability to precisely control the phosphate reduction endpoint results in a large amount of phosphate being reduced to white phosphorus, which is prone to spontaneous combustion and can easily produce highly toxic chemicals such as phosphorus chloride in acidic environments, posing significant safety hazards during the production process.
[0006] As mentioned above, it is necessary to develop an integrated recycling technology for monazite smelting, which can solve the problem that some rare earth phosphates in monazite cannot be decomposed at low temperatures, and also solve the problem that maintaining redox reactions at excessively high temperatures will lead to excessive energy consumption in the production process. Summary of the Invention
[0007] To address the aforementioned problems, the inventors discovered that by pressing monazite and reducing carbon powder into spheres, followed by flash evaporation and Joule heating (FJH), the high-temperature instantaneous reduction and pyrolysis of FJH effectively destroys the insoluble crystalline structures of monazite, such as xenotime. Then, oxygen-enriched air is introduced to oxidize phosphorus. The tail gas is washed with water to recover phosphoric acid. The reacted spheres are then crushed and acid-dissolved to separate and remove radioactive elements, followed by concentration. This method achieves high recovery rates of rare earth elements such as yttrium and radioactive elements such as uranium, eliminates the safety hazard of white phosphorus, significantly improves the leaching activity of heavy rare earth elements such as yttrium (Y) and uranium (U) encapsulated in acid-insoluble residue, and achieves high rare earth recovery rates, high radioactive element recovery rates, and high phosphorus recovery rates. It avoids phosphorus hazards, produces less waste liquid, and is precise, controllable, and energy-efficient, thus completing this invention.
[0008] The purpose of this invention is to provide an integrated monazite smelting and recycling technology based on FJH (Flash Joule Heating). The technology involves flash joule heating (FJH) of pressed monazite powder and reducing carbon powder. Through high-temperature instantaneous reduction and pyrolysis of FJH, the crystalline structure of insoluble phosphate rock and other minerals in monazite is effectively destroyed, thereby improving the leaching activity of heavy rare earth elements such as yttrium (Y) and uranium (U) encapsulated in acid-insoluble slag. Then, oxygen-enriched air is introduced to oxidize phosphoric acid, and the tail gas is washed with water to recover phosphoric acid.
[0009] Preferably, the pressed pellets of monazite powder and reduced carbon powder are subjected to flash joule heating (FJH) under an inert atmosphere. The inventors have discovered that flash Joule heating (FJH) is a technique that utilizes the Joule effect to rapidly convert electrical energy into heat energy, inducing material evaporation or phase change in an extremely short time. An FJH device typically includes a flash chamber, a vacuum valve, a diode inductor, a capacitor bank, and a voltage indicator. Its working principle involves using a capacitor-driven high-voltage discharge to heat the precursor. The sample is placed in a quartz or ceramic tube between two electrodes and can be heated under atmospheric pressure or vacuum conditions. The temperature and duration are controlled by adjusting the conductivity between the electrodes, the capacitor voltage, and the switching time. FJH heating is rapid, reaching 3000°C within 1 second, with heating and cooling rates up to 10... 5 -10 6 The process utilizes K / s and allows for precise temperature control within 3000℃. It is environmentally friendly, energy-efficient, requires no solvents or reaction gases, and is suitable for large-scale production. By employing flash Joule heating and its high-temperature instantaneous reduction pyrolysis, it can effectively destroy the insoluble crystal structures of pyroxene, such as xenotime, in monazite, thereby improving the leaching activity of heavy rare earth elements such as yttrium (Y) and uranium (U) encapsulated in acid-insoluble slag.
[0010] In a preferred embodiment of the present invention, the flash Joule heating conditions are as follows: the distance between the two electrodes is 5-15 mm, more preferably 8-12 mm; the packing density is 1.2-1.8 g / cm³, more preferably 1.3-1.6 g / cm³; the applied pulse voltage is 100-250 V, preferably 180-230 V; the pulse width is 10-500 ms, preferably 200-400 ms; and the current density is preferably ≥900 A / mm², more preferably 1000-1400 A / mm², so that the material is instantly heated to 1400-3000°C within 0.1-2 seconds; the high-temperature reaction is maintained for 1-60 seconds, preferably 10-40 seconds, so that the rapid reduction and cracking of monazite is achieved through the Joule heating effect. In a preferred embodiment of the present invention, the flash Joule heating reaction process is carried out in an inert atmosphere, and the resulting phosphorus-containing flue gas is introduced into the exhaust gas treatment system through a closed pipeline.
[0011] For an inert atmosphere, non-reactive gases such as nitrogen, helium, neon, and argon can be used.
[0012] In a further preferred embodiment, after the flash joule heating reaction, low-temperature (oxygen-rich) air is introduced for an oxidation reaction to remove phosphorus (white phosphorus / red phosphorus). The generated phosphorus oxides are recovered by washing with water, thereby avoiding phosphorus hazards and improving phosphorus recovery rate.
[0013] For low-temperature (oxygen-rich) air, the temperature is preferably 150-200℃, more preferably 150-180℃, and the oxygen content is preferably 21-31%, more preferably 25-30%.
[0014] The reaction time for low-temperature (oxygen-rich) air is preferably not less than 10 minutes, and more preferably 10-15 minutes.
[0015] The flue gas after low-temperature (oxygen-enriched) air reaction contains P2O5, and phosphoric acid is recovered by water washing. Preferably, the flue gas is treated by a two-stage water washing adsorption tower, with the water washing temperature preferably being 40-80℃, more preferably the first-stage water washing temperature being 60-80℃ and the second-stage water washing temperature being 40-60℃, and the first-stage water washing temperature being 20℃ higher than the second-stage water washing temperature, in order to obtain industrial phosphoric acid product.
[0016] Through extensive experiments, the inventors discovered that, in order to promote the full reaction of monazite, it is more advantageous to granulate monazite powder with reducing carbon powder.
[0017] In a preferred embodiment of the present invention, the monazite powder is ground to a particle size of less than 45 μm, with the fraction exceeding 95 wt%; the reduced carbon powder is ground to a particle size of 0.05-0.1 mm, wherein the carbon powder with a particle size of less than 0.08 mm accounts for more than 50%, in order to facilitate the effective mixing of the monazite powder and the reduced carbon powder and to allow for sufficient reaction in the subsequent process.
[0018] In this invention, reducing carbon powder with a high fixed carbon content can be used, such as coke powder, coal, coke, semi-coke, etc., with semi-coke being preferred.
[0019] In a preferred embodiment of the present invention, the semi-coke preferably has a fixed carbon content of 85% or more.
[0020] In this invention, the ratio of reducing toner to monazite is by mass, preferably monazite:toner = 1:0.35-0.5, more preferably monazite:toner = 1:0.38-0.47.
[0021] To briquette monazite powder and carbon powder, a binder can be used to mix them before briquetting.
[0022] Organic binders, such as modified starch and modified cellulose binders, are preferred as binders because they will volatilize and release during subsequent reactions without affecting the reaction of rare earth elements and radioactive elements.
[0023] The inventors have discovered that the preferred amount of binder is 3%-11.8% of the total mass of monazite and carbon powder, more preferably 7%-10%.
[0024] For briquetting equipment, no special briquetting equipment is needed. Commonly used briquetting equipment in this field can be used to press the mixed powder of binder, monazite powder, and carbon powder into spherical or irregularly shaped granules. The maximum geometric length of the pressed shape should not exceed 20 mm. To facilitate the transportation and filling of the pressed material, the packing porosity of the pressed granules is preferably not less than 25%, with a compressive strength of 50 N / granule, preferably greater than 100 N / granule, a pulverization rate of less than 1.5% when the number of stacked layers is greater than 50, and a bursting rate of less than 12% when baked at 300℃.
[0025] After the pressed particles undergo a flash joule heating reduction reaction, the sparingly soluble rare earth element phosphates are fully destroyed, becoming acid-soluble substances. Furthermore, the radioactive elements encapsulated within are released and can be dissolved by acid, significantly improving the acid leaching activity of rare earth and radioactive elements, thereby increasing the recovery rate of rare earth and radioactive elements.
[0026] After being subjected to a flash joule heating reduction reaction, the compressed granules are broken down and dissolved in acid.
[0027] In a preferred embodiment of the present invention, the crushing is carried out at a low temperature, preferably below 40°C, and the particle size of the crushed powder is preferably below 46 μm.
[0028] In a preferred embodiment of the present invention, acid dissolution is preferably carried out using hydrochloric acid, preferably concentrated hydrochloric acid, such as 1 mol / L or more, preferably 3 mol / L or more, more preferably 5 mol / L or more, and most preferably 6-10 mol / L.
[0029] It is preferred to use excess hydrochloric acid for dissolution, and the solid-liquid ratio is preferably 1:3-1:8 by mass.
[0030] In the acid dissolution process, preferably with a pH less than 1.5, the reaction is carried out at 80-100℃ with stirring for 1-3 hours, followed by filtration to obtain a mixed rare earth chloride solution and acid slag. The mixed rare earth chloride solution is then subjected to radioactive separation to recover rare earth elements, while the acid slag is stored or landfilled as radioactive waste.
[0031] Radioactive separation of mixed rare earth chloride solutions can be achieved through extraction, resin adsorption, alkaline precipitation, and other methods.
[0032] As an extractant, commonly used extractants in the field, such as P507 extractant, can be used.
[0033] As the adsorption resin, commonly used adsorption resins in this field, such as alkaline resins, can be used.
[0034] As a precipitating alkali, commonly used alkalis in this field, such as NaOH solution, can be used.
[0035] Regarding concentrated rare earth elements, the solution after impurity removal can be concentrated by methods such as evaporation to crystallize rare earth chloride.
[0036] The present invention has the following beneficial effects: (1) By using FJH high-temperature instantaneous reduction pyrolysis, the crystal structure of insoluble phosphate rock and other minerals in monazite is effectively destroyed, which significantly improves the leaching activity of heavy rare earth elements such as yttrium (Y) and uranium (U) encapsulated in acid-insoluble slag, thereby improving the rare earth recovery rate and the radioactive element recovery rate. (2) The wet metallurgical process of the filtrate after acid dissolution is optimized to further improve the recovery rate of rare earth elements and radioactive elements, make full use of associated radioactive resources, achieve high comprehensive resource recovery rate, and improve economic efficiency; (3) The reaction conditions are precisely controlled in the FJH reduction stage, and the hazards of white phosphorus / red phosphorus are eliminated by low-temperature oxidation. Phosphorus is efficiently converted into phosphorus pentoxide flue gas, and industrial phosphoric acid products are recovered through a water washing adsorption system, which improves the utilization rate of phosphorus resources. (4) The traditional alkaline decomposition process, which is highly polluting and water-intensive, has been abandoned. Sodium hydroxide is not required, which greatly reduces the amount of radioactive wastewater (especially high-salt and high-emission wastewater) generated and the subsequent treatment burden from the source.
[0037] (5) The overall process is green and mild, which reduces the risk of equipment corrosion and dependence on high pressure and strong corrosion equipment, and reduces the amount of hazardous chemicals (such as high concentration of alkaline solution and excessive acid) used. (6) Taking full advantage of the characteristics of FJH, which has extremely fast heating, from milliseconds to 3000℃, precise temperature control, relatively low energy consumption, no need for reaction gas, environmental friendliness and suitability for powder processing, it realizes efficient and rapid deconstruction of monazite, is easy to realize modular and miniaturized design, adapts to the relatively small scale of the monazite smelting industry, and is conducive to promotion and application. Detailed Implementation
[0038] The present invention will now be described in detail through specific embodiments, and the features and advantages of the present invention will become clearer and more explicit with these descriptions.
[0039] Example 1 Raw material: 250g monazite concentrate (rare earth oxides REO 55.2% (Y 3.2%), U 0.48%, Th 8.1%, P2O5 25.5%, the remainder being Fe2O3, CaO, MgO, SiO2, Al2O3, etc.) Step 1-1: Grinding and Mixing Monazite concentrate was pulverized using an air jet mill to D 90 =38μm (measured by laser particle size analyzer), specific surface area 510m² 2 / kg (BET method).
[0040] The semi-coke (90.2% fixed carbon, 6.5% ash) used as reducing carbon powder was ultra-finely pulverized to D... 50 =0.07mm, of which powder particles with a diameter of less than 0.08mm account for 68%.
[0041] Monazite powder and carbon powder were mixed evenly at a mass ratio of monazite:carbon powder of 1:0.45, and the coefficient of variation (CV) was 3.8% (XRF multi-point sampling analysis).
[0042] Steps 1-2: Pressing and Molding Hydroxypropyl methylcellulose (viscosity 4000 mPa•s), used as a binder, was pregelatinized and sprayed into the mixture powder obtained in step 1-1 at 8% of the total mass of monazite powder and toner.
[0043] Then, it is formed into Φ12mm×8mm ellipsoids by a roller briquetting machine. The compressive strength of a single sphere is 135±15N, the packing porosity measured by the mercury porosity method is 30±2%, and the bursting rate is 8.2% after circulating hot air at 280℃ for 40min.
[0044] Step 2: FJH flash joule heating Reactor parameters: electrode spacing 10mm, packing density 1.5g / cm³ 3 Inert atmosphere: high-purity argon (O2<50ppm), flow rate 5L / min; Electrical parameters: pulse voltage 200V, pulse width 300ms, current density 1200A / mm².
[0045] Heating reaction: The temperature was raised to 1850℃ within 50ms and held for 15s; the reaction endpoint was determined by a sharp drop in the P2O5 concentration in the tail gas as monitored by online mass spectrometry; after the heating reaction, oxygen-enriched air (25% O2) at 150℃ was introduced for oxidation for 10min, and the residual phosphorus conversion rate was 99.92% (XRF analysis); the P2O5-containing flue gas after oxidation was subjected to a two-stage water scrubbing tower (first stage 60℃, second stage 40℃), the circulating liquid pH=1.8, the P2O5 capture rate was 96.3%, and 24.5wt% H3PO4 was obtained (titration verification).
[0046] Step 3: Crushing and Acid Dissolving Mill the ball after the reaction in step 2 to D. 90 = 40μm, dissolved in hydrochloric acid. Dissolution conditions: hydrochloric acid concentration 6mol / L, liquid-to-solid ratio 4:1 (mass ratio), stirred at 95℃ for 2h, endpoint pH=0.9, filtered, and the filtrate was obtained. ICP-MS analysis showed that the rare earth leaching rate (relative to monazite leaching rate) was 98.7%, the yttrium (Y) leaching rate was 97.5%, and the liquid scintillation analysis showed that the uranium leaching rate was 90.8%.
[0047] Step 4: Separation of radioactive materials Uranium extraction: The filtrate was subjected to 201×7 strong base anion exchange resin (adsorption capacity 125 mg U / g), with a uranium adsorption rate of 99.2%. Na2CO3 was used for desorption to obtain uranium concentrate, and 1.275 g of uranium octoxide was recovered, with a uranium recovery rate of 90.1%.
[0048] Thorium precipitation: The pH of the filtrate was adjusted to 4.3 with NaOH solution to obtain Th(OH)4 precipitate. The precipitate was collected by filtration and dissolved with 7mol / L nitric acid to obtain 42.90g of nuclear-grade thorium nitrate (purity 99.95%), of which 18.02g was thorium. The overall recovery rate of thorium was 89.0%.
[0049] A total of 29.8 g of radioactive waste acid-soluble residue was obtained (accounting for 11.9% of the raw materials), with a specific activity of 1.2 × 10⁻⁶. 4 Bq / kg.
[0050] Step 5-1: Purification The filtrate obtained in step 4 was extracted with P507 (2-ethylhexylphosphonic acid mono-2-ethylhexyl ester), and 0.55g of barium sulfate was added for co-precipitation to remove radium.
[0051] Step 5-2: Crystallization The aqueous phase obtained in step 5-1 was evaporated and crystallized, and concentrated to 46.8% rare earth oxide (REO) using an MVR evaporator. The resulting crystallized rare earth chloride (REO purity 99.6%, moisture 2.5%) was obtained.
[0052] Overall recovery rates: rare earth 96.8%, uranium 90.1%, phosphorus 93.7%, thorium 89.0%, yttrium 96.5%.
[0053] Example 2 Raw material: 300g monazite concentrate (rare earth oxides REO 53.8% (Y 3.1%), U 0.42%, Th 10.2%, P2O5 24.15%) Step 1-1: Grinding and Mixing Monazite ore was pulverized using an air jet mill to D 90 =35μm (laser particle size analyzer), specific surface area 530m² 2 / kg (BET method).
[0054] The coke powder (88% fixed carbon, 6.5% ash) used as reducing carbon powder was ultra-finely pulverized to D... 90 =0.06mm, with particles smaller than 0.08mm accounting for 75%.
[0055] The monazite powder and toner were mixed for 75 minutes at a mass ratio of monazite:toner = 1:0.40. The uniformity CV was 3.2% (XRF multi-point analysis).
[0056] Steps 1-2: Pressing and Molding Hydroxymethyl cellulose (viscosity 3500 mPa•s) organic binder was added to a mixture of monazite powder and carbon powder at 6.5% of their combined mass. The mixture was then shaped into Φ10mm×10mm cylinders using a roller briquetting machine. The compressive strength of a single sphere was 155±10N (universal testing machine), and the packing porosity was 28±1.5% (mercury porosity method). After drying in hot air circulation at 260℃ for 45 minutes, the bursting rate was 6.8%. Step 2: FJH flash joule heating Reactor parameters: Electrode spacing 8mm, packing density 1.6g / cm³ 3 Inert atmosphere: high-purity nitrogen (O2 < 30 ppm), flow rate 6 L / min; Electrical parameters: pulse voltage 230 V, pulse width 200 ms, current density 1400 A / mm² 2 .
[0057] Heating reaction: The temperature was raised to 2200℃ within 40ms (infrared pyrometer) and held for 30s; endpoint determination: P2O5 concentration in the tail gas <50ppm (online mass spectrometry); after the heating reaction, oxygen-enriched air (30% O2) at 180℃ was introduced for oxidation for 12min, and the residual phosphorus conversion rate was 99.96% (XRF); the tail gas was introduced into a two-stage water washing tower (first stage 65℃, second stage 45℃), the circulating liquid pH=1.6, the P2O5 capture rate was 95.8%, and 26.2wt% H3PO4 was obtained (titration method).
[0058] Step 3: Crushing and Acid Dissolving The reacted material from step 2 was ball-milled to D90 = 42 μm and dissolved in hydrochloric acid (8 mol / L HCl, liquid-to-solid ratio 5:1 (mass ratio), 90℃, 2.5 h). The acid dissolution endpoint pH = 0.8, rare earth leaching rate 98.9% (ICP-MS), yttrium (Y) leaching rate 98.1%, uranium leaching rate 91.5% (liquid scintillation count).
[0059] Step 4: Separation of radioactive materials Uranium extraction: The filtrate was treated with 201×7 strong base anion exchange resin (adsorption capacity 130 mg U / g), and the uranium adsorption rate was 99.5% (relative to the adsorption rate of uranium in solution). 1.35 g of uranium octoxide was recovered by desorption.
[0060] Thorium precipitation: The pH of the filtrate was adjusted to 4.5 with NaOH solution to obtain Th(OH)4 precipitate. The precipitate was collected by filtration and dissolved with 7 mol / L nitric acid to obtain 65.57 g of nuclear-grade thorium nitrate (purity 99.97%), of which 27.54 g was thorium, with a thorium recovery rate of 90.1%.
[0061] Step 5-1: Purification The filtrate obtained in step 4 was extracted with P507 (2-ethylhexylphosphonic acid mono-2-ethylhexyl ester) to remove impurities (Fe / Pb removal rate >99.5%), and 0.75g of barium sulfate was added to remove radium.
[0062] Step 5-2: Crystallization The aqueous phase obtained in step 5-1 was evaporated and crystallized, and concentrated to 48.2% rare earth oxide (REO) using an MVR evaporator. The resulting crystallized rare earth chloride (REO purity 99.7%, moisture 2.2%) was obtained.
[0063] Overall recovery rates: rare earth 97.1%, uranium 91.0%, phosphorus 94.3%, thorium 90.0%, yttrium 97.0%.
[0064] Approximately 0.5 L of radioactive wastewater and 34.5 g of radioactive acid-dissolving residue were generated (accounting for 11.5% of the raw materials, with a specific activity of 1.5 × 10⁻⁶). 4 Bq / kg), with no white phosphorus safety hazards.
[0065] Example 3 Raw material: 200g monazite concentrate (rare earth oxides REO 48.5% (Y 2.5%), U 0.35%, Th 7.2%, P2O5 22.8%) Step 1-1: Grinding and Mixing Monazite concentrate was pulverized using an air jet mill to D 90 =42μm), specific surface area 480m² 2 / kg.
[0066] The semi-coke (fixed carbon 86.3%, ash 9.4%) used as reducing carbon powder was ultra-finely pulverized to D... 90 =0.09mm, of which powder particles with a diameter of less than 0.08mm account for 55%.
[0067] Monazite powder and carbon powder were mixed at a mass ratio of 1:0.36 (monazite:carbon powder) for 50 minutes. The uniformity CV was 4.1% (XRF multi-point sampling analysis).
[0068] Steps 1-2: Pressing and Molding Modified starch, used as a binder, is added to the mixture powder obtained in step 1-1 at a mass of 10.5% of the total mass of monazite powder and carbon powder.
[0069] The material is pressed into 15mm×6mm ellipsoids with a single sphere compressive strength of 95±10N, a mercury porosity of 32±2%, and dried by hot air circulation at 250℃ for 35 minutes, resulting in a burst rate of 10.5%.
[0070] Step 2: FJH flash joule heating Reactor parameters: electrode spacing 12mm, packing density 1.3g / cm³ 3 Inert atmosphere: high-purity argon (O2<100ppm), flow rate 4L / min; Electrical parameters: pulse voltage 180V, pulse width 400ms, current density 900A / mm².
[0071] Heating reaction: The temperature was raised to 1650℃ within 80ms and held for 40s; the reaction endpoint was determined by a sharp drop in the concentration of P2O5 in the tail gas; after the heating reaction, oxygen-enriched air at 170℃ was introduced for oxidation for 15min, and the residual phosphorus conversion rate was 99.8% (XRF); the P2O5-containing flue gas after oxidation was subjected to a two-stage water scrubbing tower (first stage at 70℃, second stage at 50℃), with a P2O5 capture rate of 94.5%, yielding 22.8wt% H3PO4.
[0072] Step 3: Crushing and Acid Dissolving The ball milled product from step 2 was dissolved in hydrochloric acid under the following conditions: hydrochloric acid concentration 7 mol / L, liquid-to-solid ratio 3:1 (mass ratio), stirred at 85℃ for 3 h, with an endpoint pH of 1.2. The product was then filtered to obtain the filtrate. ICP-MS analysis showed that the rare earth leaching rate (relative to the leaching rate of rare earth elements in monazite) was 97.5%, the yttrium (Y) leaching rate was 96.3%, and the uranium leaching rate was 89.2%.
[0073] Step 4: Separation of radioactive materials Uranium extraction: The filtrate was treated with 201×7 strong base anion exchange resin (adsorption capacity 125 mg U / g). The uranium adsorption rate was 99.2%, and 0.730 g of uranium oxide was desorbed and recovered, of which 0.619 g was uranium. The overall uranium recovery rate was 88.4%.
[0074] Thorium precipitation: The pH of the filtrate was adjusted to 4.3 with NaOH solution to obtain Th(OH)4 precipitate. The precipitate was collected by filtration and dissolved with nitric acid to obtain 30.17g of nuclear-grade thorium nitrate (purity 99.92%), of which 12.67g was thorium and the thorium recovery rate was 88.0%.
[0075] A total of 25.6 g of radioactive waste acid-dissolving residue was obtained (accounting for 12.8% of the raw materials), with a specific activity of 1.0 × 10⁻⁶. 4 Bq / kg.
[0076] Step 5-1: Purification The filtrate obtained in step 4 was extracted with P507 (2-ethylhexylphosphonic acid mono-2-ethylhexyl ester), and 0.3g of barium sulfate was added for co-precipitation to remove radium.
[0077] Step 5-2: Crystallization The aqueous phase obtained in step 5-1 was evaporated and crystallized to obtain mixed rare earth chloride (REO purity 99.5%, water content 2.8%).
[0078] Overall recovery rates: rare earth 96.2%, uranium 88.4%, phosphorus 92.6%, thorium 88.0%, yttrium 95.0% (Y leaching rate 96.3%, purification loss 1.3%).
[0079] Approximately 0.3L of wastewater and 25.6g of waste residue were generated.
[0080] Comparative Example 1 Take 300g of the same monazite concentrate as in Example 2, mix it with 50% NaOH solution at a mass ratio of 1:1.5 (450g NaOH solution), and stir at 110℃ for 5h. Filtration separation: The filter cake is rare earth hydroxide, which is dissolved in 3 mol / L hydrochloric acid to pH=4 to obtain a mixed rare earth chloride solution (rare earth recovery rate 94%). Residue treatment: Dissolve in 6 mol / L hydrochloric acid to pH=2, then adsorb uranium onto the filtrate using 201×7 resin (adsorption rate 85%). Total uranium recovery rate = 94% (leaching rate) × 85% ≈ 79.9%; Thorium precipitation: After adjusting the pH to 4.5, the Th(OH)4 precipitate recovery rate was 80%. Phosphorus treatment: Unrecovered phosphorus partially generates white phosphorus, which requires additional oxygen oxidation (increasing energy consumption).
[0081] Rare earth recovery rate: 94%; uranium recovery rate: 79.9%; thorium recovery rate: 80%. It generates 2.5L of radioactive wastewater and 105g of radioactive waste residue, posing a significant safety hazard due to white phosphorus.
[0082] Comparative Example 2 Take 200g of the same monazite concentrate as in Example 3, mix it with 50% NaOH solution at a mass ratio of 1:1.4 (280g NaOH solution), and react at 105℃ for 4.5h; Filtration: Rare earth hydroxide was dissolved in acid to pH=4, with a rare earth recovery rate of 93.5%; The residue was acid-dissolved to pH=2, and the resin adsorbed uranium (adsorption rate 82%). The total uranium recovery rate was approximately 76.7% (93.5% × 82%). Thorium recovery rate was 78%, phosphorus was not recovered.
[0083] Rare earth recovery rate was 93.5%, uranium recovery rate was 76.7% (lower than 88.5%), and yttrium recovery rate was 89.8%. A total of 1.8L of wastewater and 82g of waste residue were generated, and the energy consumption was 30% higher than that of Example 3.
[0084] The present invention has been described in detail above with reference to specific embodiments and / or exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A comprehensive recycling technology for monazite smelting based on FJH, wherein monazite powder and reducing carbon powder are pressed into balls and subjected to flash joule heating. Through high-temperature instantaneous reduction pyrolysis using FJH, the crystalline structure of insoluble phosphate rock and other minerals in monazite is effectively destroyed, thereby improving the leaching activity of heavy rare earth elements such as yttrium (Y) and uranium (U) encapsulated in acid-insoluble slag. Low-temperature (oxygen-rich) air is then introduced to oxidize phosphoric acid, and the tail gas is washed with water to recover phosphoric acid.
2. The technology according to claim 1, wherein, In an inert atmosphere, pressed balls of monazite powder and reducing carbon powder are subjected to flash joule heating.
3. The technology according to claim 2, wherein, An inert atmosphere can be achieved using non-reactive gases such as nitrogen, helium, neon, and argon.
4. The technology according to claim 1, wherein, By controlling the flash Joule heating conditions, the material is instantly heated to 1400-3000℃ within 0.1-2 seconds; the high-temperature reaction is maintained for 1-60 seconds, preferably 10-40 seconds, to achieve rapid reduction and cracking of monazite through the Joule thermal effect.
5. The technique according to claim 1, wherein the flash Joule heating conditions are as follows: the distance between the two electrodes is 5-15 mm, more preferably 8-12 mm; the filling density is 1.2-1.8 g / cm³, more preferably 1.3-1.6 g / cm³; the applied pulse voltage is 100-250 V, preferably 180-230 V; the pulse width is 10-500 ms, preferably 200-400 ms; and the current density is preferably ≥900 A / mm², more preferably 1000-1400 A / mm².
6. The technology according to claim 1, wherein, The temperature of the low-temperature (oxygen-rich) air is 150-200℃, preferably 150-180℃. The oxygen content in low-temperature (oxygen-rich) air is preferably 21-31%, more preferably 25-30%.
7. The technology according to claim 1, wherein, The reaction time for low-temperature (oxygen-rich) air should be no less than 10 minutes, preferably 10-15 minutes.
8. The technology according to claim 1, wherein, Monazite is pulverized and ground to a particle size of less than 45μm, with the fraction exceeding 95wt%; reduced carbon powder is ground to a particle size of 0.05-0.1mm, of which carbon powder with a particle size of less than 0.08mm accounts for more than 50%, and the two are then pressed into balls.
9. The technology according to claim 1, wherein, Monazite powder and reducing carbon powder are mixed with a binder and then pressed into balls. Organic adhesives are used as binders; The amount of binder is 3%-11.8% of the total mass of monazite and carbon powder, preferably 7-10%.
10. The technology according to claim 1, wherein, The monazite powder and reducing carbon powder, after being subjected to the FJH high-temperature instantaneous reduction and pyrolysis reaction, are pressed into balls, crushed, dissolved in acid, and the radioactive materials are separated and then concentrated.